(untitled) (Per Musi, 2000)
This paper discusses the hermeneutic status of musical performance, starting from two opposite and well known conceptions: 1) one which sustains strict fidelity to the composer; 2) another confers total license to the performers. In opposition to both, the author asserts that the guide to a genuine interpretation is the musical work itself, not the composer’s or the performer’s intentions. To support her assumptions, she brings up Luigi Pareyson’s interpretation theory comparing his thesis with the above-mentioned conceptions and examines its application to the subject.